Soportes del vidrio recubiertos con poli-L-lisina para analizar materiales biológicos en partículas tanto al microscopio electrónico de rastreo como al de transmisión - Hernández, Francisco; Akahori, Hiroshi; Brenes, Fernando (Revista de Biología Tropical, 1986)
The use of poly-L-lisine solutions to form policathionic membranes on micro cover glass, acting as an adhesive medium for biological particulate specimens (ej. bacteria, yeast and isolated cells) is described. Adhered specimens to cover glass were fixed, dehydrated, dryed to critical point and covered again with platinum-carbon or gold, and then, they were placed under a scanning electron microscope. Later, a sample was digested in sodium hypochlorite, separating the metal layer representing the replica of sample. lt was collected on a copper grid and it was analyzed by transmision electron microscope.